A fight for life and dignity: A case of massive traumatic brain injury and the paths for treatment and neurorehabilitation. Issue 1 (March 2016) - Shklovsky, Viktor M.; Zotova, Lybov I.; Malyukova, Natalia G.; Mamicheva, Elena D.; Petrushevsky, Alexey G.; Mayorova, Larisa A.; Syrnikova, Bela A.
Abstract : We present a clinical case of treatment and neurorehabilitation of a patient with severe neurological deficit due to extensive traumatic lesion of the left hemisphere of the brain. Until recently, such cases were considered incurable and remained marginalized throughout their lives. This clinical case illustrates the compensatory brain possibilities under long‐term integrated multidisciplinary treatment and neurorehabilitation with mandatory application of medical, medico‐psychological, medico‐pedagogical, and medico‐social methods, the importance and intensity of which vary at different stages of the disease. This process is addressed in the individual patient. The greatest efficiency of the neurorehabilitation treatment of patients with severe consequences of a stroke and traumatic brain injury can be reached under the following conditions: the earliest possible start of rehabilitation with a sufficient duration and intensity; interdisciplinary and integrative rehabilitation process at various stages of rehabilitation treatment; systematic clinical and neuropsychological diagnostics; systematic monitoring of somatic, neurological, psychiatric, and psychological condition of the patient; assistance with sociopsychological and labor issues; and problem‐solving support.